Off the Beaten Path: Caring for People Engaging in Potentially Unsafe Low Evidence Therapies. (February 2023) - Hammond, John; Schneiderhan, Jill; Taylor, Laura; Marks, Adam
Palliative care clinicians regularly care for patients with serious illnesses, many of whom are engaging in the use of complementary and alternative medicine (CAM) either alone or along with conventional medical therapies. A subset of these patients may be engaging in therapies that have little or no evidence for efficacy and carry significant potential risks to their health. These therapies, however, may carry a great deal of significance for the patient and family for whom conventional medicine has failed or is otherwise deemed untenable. Dismissing such therapies as "quackery" risks alienating patients and damaging or even severing a therapeutic relationship. When faced with patients who are engaging in potentially unsafe low-evidence therapies (PULETs), clinicians themselves may experience a great deal of moral distress when deciding how to balance supporting the hope PULETs may represent with the principles of nonmaleficence and autonomy. In this article, we will review the definition of PULETs and distinguish them from most CAM therapies. Drawing upon existing writings in the CAM literature, we will then review a framework to evaluate the relative risk/benefit ratio of such therapies followed by a review of the ethical and legal aspects of care. Finally, utilizing existing principles and tools in emotion-based communication, we present a communication approach to foster continued collaboration and care for patients who engage in PULETs.